(untitled) - Kotter, John P. (Boston, Massachusetts, 2014)
Accelerate (XLR8) vividly illustrates the five core principles underlying the new network system, the eight Accelerators that drive it, and how leaders must create urgency in others through role modeling. And perhaps most crucial, the book reveals how the best companies focus and align their people’s energy and urgency around what Kotter calls the big opportunity.
Keywords: Kế hoạch chiến lược,Strategic planning